Lean empowerment and respect for people : the evolution of lean production systems - Gundlach, Trevor (Routledge, Taylor & Francis Group, 2024)
There are two pillars of a Lean Management System: Continuous Improvement and Respect for People. Most books about Lean Production have focused overwhelmingly on Continuous Improvement and fail to treat Respect for People as an equal pillar. It is overlooked or understated, resulting not in a Lean house, but in a lean-to structure. It is our responsibility to level out the structure once again. The study of people is messy and exciting. It demands that we explore multiple interdisciplinary studies, including psychology, sociology, philosophy, and even theology. This book runs a parallel course with Lean Production but has a different goal. Instead of production, efficiency, and financial gains, our goal is to understand the reasons why staff come to work in the morning. We can only understand a system when we understand its people. They own the culture. Lean must therefore evolve from a Production System into an Empowerment System. Lean Production will no longer serve the contemporary workforce; knowledge workers, if you are reading this, you are likely a knowledge worker who deserves more than a repackaging of the same ideas. You are not a line worker, and your system should not treat you as such. Therefore, we need a new system. One that prioritizes Respect for People over Continuous Improvement. Leaders in this system must recognize belonging and psychological safety as preconditions to process innovation. New definitions of value and waste--the staples of Lean philosophy--must take on a more human face and propel the change of culture. We must flip Lean on its head for the sake of our modern workforce.
Keywords: Lean manufacturing.; elektronické knihy; electronic books